2010
DOI: 10.1007/s00586-009-1258-4
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome of computer-assisted spinal pedicle screw placement: a systematic review and meta-analysis of 23 studies including 5,992 pedicle screws

Abstract: A number of studies have shown increased accuracy of pedicle screw placement in spine with the help of computer-assisted navigation. The literature is lacking in regard to functional benefit derived from this technique. The aim of this systematic review was to look at the functional outcomes following computer-assisted pedicle screw placement in spine. A 'Dialog Datastar' search was used using optimized search strategy covering the period from 1950 to July 2009; 23 papers were finally included which met our in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
121
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(136 citation statements)
references
References 40 publications
6
121
1
2
Order By: Relevance
“…In conclusion, both in vivo and in vitro subgroups revealed that navigation method obtained a significant lesser pooled risk of pedicle violation compared with the conventional method (P \ 0.05). The results were consistent with those of Kosmopoulos and Schizas, Verma et al [8,56] (Fig. 1).…”
Section: Navigation Methods For Pedicle Screw Insertionsupporting
confidence: 92%
See 2 more Smart Citations
“…In conclusion, both in vivo and in vitro subgroups revealed that navigation method obtained a significant lesser pooled risk of pedicle violation compared with the conventional method (P \ 0.05). The results were consistent with those of Kosmopoulos and Schizas, Verma et al [8,56] (Fig. 1).…”
Section: Navigation Methods For Pedicle Screw Insertionsupporting
confidence: 92%
“…Navigation provided a higher accuracy in the placement of pedicle screws for most of the subgroups presented. In a pooled analysis of 14 comparative studies on pedicle screw insertion, Verma et al [56] also demonstrated a significant advantage in terms of accuracy of navigation over conventional methods. The limitation was that the two reviews analyzed different navigation methods together, and drew pooled navigated pedicle screw insertion accuracy.…”
Section: Navigation Methods For Pedicle Screw Insertionmentioning
confidence: 99%
See 1 more Smart Citation
“…The computer-assisted navigation system has been gradually applied into spine surgeries [7]. However, the natural value of the navigation system in the spinal surgical procedure was questioned [8]. Recent studies suggested that the accuracy of the pedicle screw placement in the lower thoracic and lumbar spine could be improved with a navigation system [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of pedicle screw implantation using these techniques varies considerably in the literature (from 28 to 94 %), though the evidence generally favors the use of image-guidance systems [5,10,25,27]. A miniature spine-mounted robot has recently been developed to further improve the accuracy of pedicle screw placement [2,4,22].…”
Section: Introductionmentioning
confidence: 99%